The Effectiveness of the Probing Prompting Learning Model on the Learning Outcomes of Fiqh at Vocational High School - Azizah, Nurul; Zain, Auriza Luthfiah; Marsela, Shanya (Study Program of Arabic Language Teaching, 2023)
This research is an effort to improve fiqh learning using the probing prompting learning model to increase effectiveness in the learning system at the vocational school level. Through this approach students can develop a deep understanding of fiqh concepts more interactively and reflectively. Students need to understand religious concepts more maturely at the vocational school level. This study used an experimental research method consisting of an experimental class and a control class with the technique of collecting learning outcomes using an instrument test in the form of a Posttest only and the analysis used is Mann Whitney to analyze ordinal data which may be relevant in the context of driving questions and student responses which can be measured ordinally or qualitatively, to differentiate student responses between groups that use probing prompting and the control group, which produces asymp.sig <0.05, then Ho is rejected and Ha is accepted. Then the results obtained by the researchers used the Mann-Whitney test with SPSS 25, namely 0.00 <0.05, which means that Ho was rejected and Ha was accepted that it can be concluded that the Probing Prompting Learning learning model is effective for class X student learning outcomes at SMK Muhamadiyah Sambungmacan, Central Java.